### 20 Answers

Relevance

- 8 months ago
I mightbbe totally wrong but I would do 6-2 which is 4 and multiply that times 1 which is 5-4

- 8 months ago
6-2(5-4)

To solve, solve the one in parentheses first.

6-2(1) because 5-4 = 1 (perform multiplication)

6-2 because 2(1) = 2 (perform subtraction)

4 because 6-2 = 4

Lesson: PEMDAS

- Anonymous8 months ago
the answer is 4 (use order of operations)

- How do you think about the answers? You can sign in to vote the answer.
- Anonymous8 months ago
Do 5 - 4 inside the brackets first

multiply 2 by what is inside the brackets.

then subtract the above from 6

4 is what you should get.

- Donnie PorkoLv 78 months ago
4. Parenthesis goes first so 5-5 = 1. Then multiplication goes next so 2(1) = 2. Finally 6 - 2 = 4.

Still have questions? Get your answers by asking now.